Innovating in less developed regions: What drives patenting in the lagging regions of Europe and North America - Rodríguez‐Pose, Andrés; Wilkie, Callum (Growth and change, 2019)
Not all economically disadvantaged—“less developed” or “lagging”—regions are the same. They are, however, often bundled together for the purposes of innovation policy design and implementation. This paper attempts to determine whether such bundling is warranted by conducting a regional level investigation for Canada, the United States, on the one hand, and Europe, on the other, to (a) identify the structural and socioeconomic factors that drive patenting in the less developed regions of North America and Europe, respectively; and (b) explore how these factors differ between the two contexts. The empirical analysis, estimated using a mixed‐model approach, reveals that, while there are similarities between the drivers of innovation in North America's and Europe's lagging regions, a number of important differences between the two continents prevail. The analysis also indicates that the territorial processes of innovation in North America's and Europe's less developed regions are more similar to those of their more developed counterparts than to one another.